Developmental family functions and cognitive emotion regulation in adolescents with conduct disorder and normal peers - Zahra Bakht Shokuhi; Behzad Shalchi; Ayyoub Malek; Saber Pour Hasan; Shahrokh Amiri (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2025)
Background. Conduct disorder is a common adolescent behavioral disorder influenced by family upbringing, associated with impaired emotion regulation. This study compared family functioning and cognitive emotion regulation in adolescents with conduct disorder and their typically developing peers. Methods. This descriptive-analytical cross-sectional study was conducted in 2023 in Tabriz. The study populations were adolescents aged 15-18 years attending school in Tabriz, selected using a multi-stage cluster sampling method. 375 students responded to the Youth Self-Report (YSR) questionnaire, and 30 participants were selected as the conduct disorder group and 30 as the control group. Then, they completed tools assessing family developmental functioning and cognitive emotion regulation. Data were analyzed using SPSS software. Results. Adolescents with conduct disorder perform poorly in most aspects of family developmental functioning (such as attention and regulation, intimacy, social problem-solving, and discipline). Additionally, these adolescents tend to use negative emotion regulation strategies, such as catastrophizing and self-blame, more frequently, while they perform weaker in positive strategies like positive reappraisal and refocusing. The results of all MANOVA significance tests were positive, indicating that the subscales of family developmental functioning and cognitive emotion regulation strategies have a multivariate effect on the severity of conduct disorder symptoms. Conclusion. This study highlights the negative impact of conduct disorder on family functioning and emotion regulation. Enhancing family dynamics and cognitive emotion regulation skills may help reduce its symptoms in adolescents. Practical Implications. This study highlights the need for psychological interventions to enhance emotion regulation and family functioning, reducing conduct disorder symptoms in adolescents.